Foundry Mould Discovered at Excavation CXCIX of Bolgar Fortified Settlement - Zorya Roman S. (Поволжская археология, 2018)
The paper introduces into scientific discourse a split stone foundry mould discovered a result of activities of 2014 at excavation No. CXCIX of Bolgar settlement. It belongs to the closed type and consists of two flaps, each of which has two working planes. The mould contains seven grooves for the production of closed lunulas of a closed type, one of them contains an inscription in Naskh script. The main adjacent working planes of the mould feature a smelting groove for moulding a hollow bracelet – imitation of the renowned braided bracelets with interwoven filigree. The ends of such articles have the shape of animal heads. The author concludes that it was manufactured with the use of the “splashing”. The finding in question was discovered in the layer of Bolgar settlement dated the 1320–40s.